P4 Community food production in small island developing states: a systematic scoping review of health, social, economic and environmental impacts. (September 2018) - Haynes, E; Brown, C; Wou, C; Vogliano, C; Guell, C; Unwin, N
Abstract : Background: Small island developing states (SIDS) have some of the highest rates globally of obesity, diabetes and related non-communicable diseases. A diet of energy dense and highly processed foods over fruit, vegetables and fibre is a major determinant of this burden. The majority of SIDS lack food sovereignty, are vulnerable to food insecurity and rely heavily on food imports. The need to increase local food production, particularly of non- or minimally processed foods, is seen as a pre-requisite to effective long term NCD prevention. This research aimed to explore what is known on community-based food production initiatives (CFPIs) in SIDS, including their number and distribution, characteristics, and their positive and negative impacts on health, social and economic wellbeing and the environment. Methods: A systematic scoping review was undertaken to identify literature from a range of disciplines. We searched 12 electronic databases for articles published in the last 20 years which concerned local food production initiatives in SIDS. In total, 8215 articles were screened and data abstracted for 153 eligible articles by two independent reviewers and verified by a third. Articles were included if they were set in one of 57 SIDS countries and reported health, social, economic or environmental impacts of or on CFPIs. Data abstraction and analysis focused on geographical location, type of CFPI, methodology and study design, theoretical frameworks proposed and the impacts described in each report. Results: The majority of research was conducted in the Pacific or Caribbean region (49%, 44%) and primarily focused on fishing and crop farming (39%, 26%). The findings indicate that there is a predominance of research focusing on the environmental impact of marine and costal resources (mostly fishing), and very limited evidence regarding the impact of locally implemented food production programs on human health, particularly nutrition and diet-related outcomes. Furthermore, there was a general absence of explicit theoretical frameworks or logical models to explain how CFPIs may bring about health, social, economic or environmental change. The studies which reported the impacts on CFPIs tended to report the impact of management factors, social characteristics or higher level socio-political environment on CFPIs and subsequent food security. Conclusion: Evidence of the health and other impacts of CPFIs in SIDS is limited and the approaches taken inconsistent. This review demonstrates the need and provides a basis for developing a coherent body of methods to examine the impacts of CFPIs and provide evidence to guide policy.